Assessment of Frost Depth in Romania - Arion Cristian; Vacareanu Radu; Aldea Alexandru; Arion Andrei; Pavel Florin (E3S Web of Conferences)
The study of severe climate and weather conditions has accelerated in recent decades, partly due to political engagement. However, historical climate monitoring data has not received sufficient attention. Reliable assessments of the maximum extent of soil freezing are crucial for determining construction costs and building foundations. Structural designers also require reliable local meteorological data. This study presents calculations of these parameters for Cluj Napoca city. For instance, a revised frost depth map for Romania is necessary due to recent climate studies indicating a rise in both regional and global surface temperatures, with the most notable warming for the previous thirty years. The findings from this investigation could help reduce frost-related disasters and inform policies and measures for adapting geotechnical and structural designs in Romania.